Prolonged Sitting Causes Lower Back Pain For Nursing Students In Yogyakarta, Indonesia - Natalia Ririn Kalumbang; Januar Rizqi; Nur Alvira Pascawati (Jurnal Keperawatan Respati Yogyakarta, 2020)
Individuals who spend most of their time sitting for long periods are at risk of experiencing low back pain. Pain complaints are the most common injuries in the work environment, both as administrator and in academia. The purpose of this study was to determine the relationship between the lengths of sitting during lectures with complaints of low back pain. This research is a quantitative analytic cross-sectional design conducted on 62 nursing students. Sitting time and pain complaints were measured using a questionnaire, physical examination (laseque test) and descriptive scale verbal pain assessment instrument (VDS). Data analysis used Fisher exact test with α: 5%. The results showed that the number of respondents who experienced low back pain complaints was 44 (71.0%) with a sitting time of ≥5 hours is 51 (82.3%) with a value of p = 0.025. The conclusion of this research is the length of sitting during lectures is at risk of causing low back pain